EFFECTIVENESS OF COLLECTIVE MANAGEMENT ORGANIZATION IN COLLECTIVE ROYALTIES OF MUSIC AND COPYRIGHT WORK ON KARAOKE BUSINESS ACHIEVEMENT BASED ON LAW NUMBER 28 YEAR 2014 ON COPYRIGHT - Juardi, Adi; Wati, Nur (Fakultas Hukum Universitas Djuanda Bogor, 2018)
He effectiveness of Collective Management Organization (CMO) in charge royalties on business karaoke questionable, this relates to the birth of Act No. 28 year 2014 about copyright which regulate in particular the CMO. Because there are still many karaoke business which still has not fulfilled the obligation to pay royalties of works of copyright music and their songs (karaoke company) exploitation for commercial business interests. This research aims to: (1) know the role of business in addressing CMO karaoke that doesnt pay royalties, (2) know the effectiveness of CMO administering royalties on the karaoke business person under law No. 28 Year 2014, (3) knowing the efforts in improving polling CMO royalty on the karaoke business. This type of research is the Juridical Sociological (Empirical) approach to legislation as well as interviews. The results of this study showed that the effectiveness of the CMO administering royalties have not been effective because it is based on the theory of legal effectiveness Soerjono Soekanto. Efforts in improving the collection of royalties already attempted CMO. The conclusions of this research that is not yet effective because CMO factor law enforcement community and culture that Indonesia is still not law abiding. Her advice is a strict law enforcement and awareness of the law business karaoke should be improved so that effective in running in CMO.